FROM RECRUITMENT TO RETENTION: ALIGNING HR ANALYTICS AND MARKETING INSIGHTS FOR SUSTAINABLE CAMPUS PLACEMENT STRATEGIES - Shivram, Shalini; Das, Nanda; Patil, Kalyani; Varyani, Geetu; Hemnani, Deepika; Rao, Bora Umammaheshwar (Lex localis-journal of local self-government, 2025)
This research examines the integration of human resource analytics and marketing insights to develop sustainable campus placement strategies that address both recruitment and retention challenges. Using a mixed-methods approach combining quantitative analysis of placement data from 12 universities and qualitative insights from 45 industry professionals, this study proposes a novel framework for aligning traditionally siloed HR and marketing functions. Our findings reveal that institutions implementing data-driven placement strategies informed by both disciplines experienced 37% higher retention rates and 42% improved employer satisfaction. We identify four key pillars for sustainable placement ecosystems: predictive candidate-employer matching, persona-based engagement, continuous feedback mechanisms, and longitudinal performance tracking. This paper contributes to the evolving discourse on higher education-industry partnerships by demonstrating how strategic alignment of HR analytics and marketing insights can transform campus placement from transactional recruitment to sustainable talent partnerships.